The SEPALLATA-like gene HrSEP1 in Hippophae rhamnoides regulates flower development by interacting with other MADS-box subfamily genes - Cong, Di; Zhao, Xue; Ni, Chang; Li, Mengru; Han, Luwen; Cheng, Jianlin; Liu, Hongzhang; Liu, Huijing; Yao, Dan; Liu, Shuying; Chen, Guoshuang (Frontiers in Plant Science, 2025)
MADS-box genes are classified into five categories: ABCDE, including SEP1, SEP2, SEP3, SEP4, and other homologous genes, which play important roles in floral organ development. In this study, the cDNA sequence of the HrSEP1 gene was cloned by RT-PCR and confirmed that this gene belongs to the MADS-box gene family. In addition, subcellular localization experiments showed that the HrSEP1 protein was localized in the nucleus. We verified the interaction of HrSEP1 with HrSOC1, HrSVP, and HrAP1 using yeast two-hybrid and bimolecular fluorescence complementation assays. These genes jointly regulate the growth and development of floral organs. We also found a strong synergy between HrSEP1 and AP1 genes in sepals, petals, and stamens by transgenic methods and fluorescence quantitative PCR, suggesting that HrSEP1 and AP1 may co-regulate the development of these structures. In conclusion, the expression of HrSEP1 has a certain effect on the development of floral organs, and these findings lay the foundation for further research on the biological functions of MADS transcription factors in Hippophae rhamnoides.